Spontaneous vaginal birth following induction with intravenous oxytocin: Three oxytocic regimes to minimise blood loss post birth. Issue 3 (May 2021) - Lewis, Lucy; Doherty, Dorota A.; Conwell, Marion; Bradfield, Zoe; Sajogo, Monica; Epee-Bekima, Mathias; Hauck, Yvonne L.
Abstract: Background: No evidence was identified in relation to the downward titration/cessation of intravenous oxytocin post spontaneous vaginal birth, in the absence of postpartum haemorrhage (PPH); suggesting clinicians' management is based on personal preference in the absence of evidence. Aim: To determine the proportion of induced women with a spontaneous vaginal birth and PPH, when intravenous oxytocin was utilised intrapartum and ceased 15, 30 or 60 minutes post birth. Methods: This three armed pilot randomised controlled trial, was undertaken on the Birth Suite of an Australian tertiary obstetric hospital. Incidence of PPH was assessed using univariable and adjusted logistic regression, which compared the effect of titrating intravenous oxytocin post birth on the likelihood of PPH, relative to the 15 minute titration group. Findings: Postpartum haemorrhage occurred in 26% (30 of 115), 20% (23 of 116), and 22% (30 of 134) of women randomised to a 15, 30 and 60 minute titration time post birth, with no statistically significant differences between groups. Conclusion: There was no difference in the incidence of PPH between the three groups. Therefore, we question the benefit of delaying cessation of intravenous oxytocin for 60 minutes post birth. Further investigation in this cohort is recommended, to compare the incidence of PPH when intravenous oxytocin is ceased either immediately, or 30 minutes post birth. This research is warranted, as an evidence-based framework is lacking, to guide midwives globally in relation to their management of intravenous oxytocin post an induced spontaneous vaginal birth, in the absence of PPH.